Ethiopia Student Assessment : SABER Country Report 2009 - World Bank Group (World Bank, Washington, DC, 2015)
In 2009, Ethiopia joined the Russia Education Aid for Development (READ) trust fund program, the goal of which is to help countries improve their capacity to design, carry out, analyze, and use assessments for improved student learning. As part of the READ trust fund program, and in order to gain a better understanding of the strengths and weaknesses of its existing assessment system, Ethiopia participated in a formal exercise to benchmark this system under The World Bank’s systems approach for better education results (SABER) program. SABER is an evidence based program to help countries systematically examine and strengthen the performance of different aspects of their education systems. The SABER student assessment framework is built on the available evidence base for what an effective assessment system looks like. The framework provides guidance on how countries can build more effective student assessment systems. The framework is structured around two main dimensions of assessment systems: the types and purposes of assessment activities and the quality of those activities.